ANALISIS OPINI GOING CORNCERN PADA PERUSAHAAN FARMASI DI BURSA EFEK INDONESIA (Multiple Correlation Method) - Pipit Buana Sari (Jurnal Akuntansi Bisnis dan Publik, 2020)
This research is a study that tested the effect of the Company’s Growth and the Total Asset Turnover (TATO) of the acceptance of Going Concern in the pharmacy companies listed at Indonesia Stock Exchange. In this study, researchers used purposive sampling and sample size to obtain a sample of 10 pharmacy companies listed on the Stock Exchange in the year 2014-2018. Based on the results of purposive sampling, there are 5 companies that meet the criteria as a research sample. The method of analysis used was logistic regression. The results of this study indicate the Total Asset Turnover (TATO) do not affect the going concern opinion reception while Company’s Growth effect on the acceptance of going-concern opinion.